Legal Protection for Land Title Certificate Holders in Over-lapping Land Dispute Resolution in DKI Jakarta - Alexander Porwayla; Indra Yuliawan (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Legal protection for holders of Land Title Certificates (Sertifikat Hak Milik/SHM) represents a funda-mental issue in Indonesian agrarian law, particularly in DKI Jakarta where overlapping land certificates remain a persistent problem threatening the rights of landowners. This study aims to analyze the legal protection framework for certificate holders and evaluate the dispute resolution process for overlapping land title certificates. The method employed is normative juridical research with a statutory and case ap-proach, supported by six years of practical experience in non-litigious advocacy at the Awalindo Jakarta Legal Aid Institute (LBH Awalindo). The analysis integrates Gustav Radbruch’s Three Basic Values of Law: legal certainty (Rechtssicherheit), justice (Gerechtigkeit), and utility (Zweckmäßigkeit). Results show that legal protection for SHM holders is grounded in a negative publication system with a positive tendency (negatief stelsel bertendensi positif), whereby a certificate constitutes strong but non-absolute evidence of land ownership. Dispute resolution for overlapping certificates may be pursued through administrative mechanisms at the National Land Agency (BPN) or through civil litigation. Case analysis of Jakarta District Court decisions No. 278/Pdt.G/2023/PN.Jkt.Pst and No. 633/Pdt.G/2022/PN.Jkt.Pst demonstrates that courts protect good-faith certificate holders while correcting administratively defective certificates. The study concludes that strengthening the land registration system and applying restorative approaches in mediation are essential to achieving substantive justice.